2015
DOI: 10.1177/0306624x15622429
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset Offending: A Neglected Reality? Findings From a Contemporary British General Population Cohort

Abstract: There is disagreement in the literature as to whether there are any true adult-onset offenders. The aim of this study is to investigate the prevalence and correlates of adult-onset offenders in a contemporary British general population cohort consisting of 739 individuals aged between 18 and 25 years. Sixteen percent of participants reported offending for the first time after the age of 18. It is concluded that adult-onset exists and deserves to be studied further. Adult-onset offenders were more likely to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Recently, DeLisi et al (2018) have argued that the existence of AO offending has been mixed largely due to the narrow focus on early adulthood (Krohn et al, 2013; Sohoni et al, 2014) and is primarily based on official data lacking triangulation with self-report data (Zara & Farrington, 2010). The results of this study suggest that AO offending may exist and deserves further study as suggested by several authors (DeLisi & Piquero, 2011; Eggleston & Laub, 2002; Sapouna, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Recently, DeLisi et al (2018) have argued that the existence of AO offending has been mixed largely due to the narrow focus on early adulthood (Krohn et al, 2013; Sohoni et al, 2014) and is primarily based on official data lacking triangulation with self-report data (Zara & Farrington, 2010). The results of this study suggest that AO offending may exist and deserves further study as suggested by several authors (DeLisi & Piquero, 2011; Eggleston & Laub, 2002; Sapouna, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Importantly, this suggests that individuals convicted in adulthood may not merely be explained by individual-level traits and/or social disadvantages in childhood, but also be understood as a result of proximate events and/or social circumstances preceding the conviction. For example, in a British cohort study, Sapouna (2017) found that adult-onset offenders tended to have experienced negative events in adulthood, such as mental illness and drug use. On a higher abstraction level, then, the controversy concerns whether criminal events in adulthood can be traced to the belonging of certain groups (such as the LCP or AL) or whether they should primarily be explained by the near context in which they are committed.…”
Section: Adult-onset Offendingmentioning
confidence: 99%
“…It was, for example, found that adult-onset offenders are relatively often involved in sex offenses, theft from work, vandalism, fraud, and carrying an offensive weapon. Compared to juvenile-onset offenders, they are less likely to be involved in robberies, burglaries, drug offenses, and (vehicle) thefts [38,56].…”
Section: Crime MIXmentioning
confidence: 99%
“…DeLisi and Piquero [8] identified this understudied group of offenders as an important research gap in life-course criminology that deserves serious research attention in the future. Also, more recently, Sapouna [56] endorsed this argument by stating that "there is a non-negligible proportion of adultonset offenders that merits further research".…”
Section: Introductionmentioning
confidence: 99%